A longitudinal analysis of morphological characteristics and body proportionality in young elite sprint paddlers - López-Plaza, D.; Manonelles, P.; López-Miñarro, P. A.; Muyor, J. M.; Alacid, F. (The Physician and Sportsmedicine, 2019)
Introduction: There are certain anthropometric attributes common to most high-level paddlers and among the determinants for optimal performance consecution in senior categories.